LATEST INNOVATION: ECO-FRIENDLY SOLID SOAP FROM COCONUT, PALM, AND OLIVE OILS - Ridona Zulyeni Putri (Pendidikan IPA, FMIPA, UNP, 2023)
Natural soaps made from vegetable ingredients are increasingly popular nowadays, especially those known as natural soaps. The vegetable oil content of plants makes it called natural) and its advantage lies in its ability to moisturize the skin without leaving potentially harmful chemical residues. The research method used is a laboratory experimental method using descriptive analysis, so that it can provide information regarding the manufacture of solid soap. In this research on making solid soap, a pH test analysis or degree of acidity was carried out. pH is used to determine the alkaline and acidic levels of a solution. Acidity is the concentration of hydrogen ions in the water solvent. Soap that has a high pH occurs due to soap hydrolysis. A good soap pH value is soap that has a pH of around 7. Organoleptic testing on solid soap that has been made is carried out by observing the aroma, amount of foam and texture of the soap. This test aims to determine the quality of the soap that has been made. Making organic solid soap is expected to be able to produce products that are safe and of course comfortable for the skin without any side effects and are environmentally friendly. Soap that has a high pH occurs due to soap hydrolysis.